2011
DOI: 10.1212/wnl.0b013e318212015e
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid PET imaging in patients with mild cognitive impairment

Abstract: Hippocampal atrophy and amyloid deposition seem to dissociate during the evolution of MCI, the atrophy increasing clearly and [(11)C] PiB retention changing modestly when conversion to AD occurs. Longer follow-up is needed to determine whether nonconverters would convert to AD later, which would suggest accelerated [(11)C] PiB retention preceding clinical conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
118
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 18 publications
11
118
1
5
Order By: Relevance
“…A study conducted in mainly APOE e4 allele carriers showed that there was no change over time in Ab deposition in converters and nonconverters to AD. However, hippocampal atrophy was worse in converters than in nonconverters, and increased significantly in both groups, 37 suggesting that a dissociation between neurodegeneration and amyloidosis can occur.…”
Section: Resultsmentioning
confidence: 97%
“…A study conducted in mainly APOE e4 allele carriers showed that there was no change over time in Ab deposition in converters and nonconverters to AD. However, hippocampal atrophy was worse in converters than in nonconverters, and increased significantly in both groups, 37 suggesting that a dissociation between neurodegeneration and amyloidosis can occur.…”
Section: Resultsmentioning
confidence: 97%
“…5 PET tracers that bind to the aggregated A␤ peptides offer promise to directly assess fibrillar amyloid pathology both visually and quantitatively. 6,7 Prior studies have found that 11 C-labeled Pittsburgh compound B ( 11 C-PiB)-positive normal subjects and subjects with MCI are more likely to show faster cognitive deterioration than PIB-negative subjects. 3,8 -16 However, the short half-life of 11 C (20 minutes) limits its use as a routine clinical test.…”
mentioning
confidence: 99%
“…Dysregulation of axonal transport might be one mechanism underlying this spatial separation (2,30). Importantly, posterior midline cortices (precuneus and PCC) are among the regions with the highest Ab load as observed in PET studies including the current study, and Ab load of the PCC predicts conversion of MCI to AD, which is accompanied by increasing hippocampal atrophy (32). In an animal model, it has been shown that experimentally induced PCC dysfunction leads to functional disconnection with the hippocampus (33).…”
Section: Discussionmentioning
confidence: 49%